The Effect of Reward, Punishment, and Leadership Exemplary on Employee Performance with Organizational Culture as an Intervening Variable - Miftahul Jannah; Nursaid Nursaid; Moh. Thamrin (UNIVED Press, 2025)
This study analyzes the performance of employees of SMK Muhammadiyah 7 (SMK MUTU) Gondanglegi, Malang Regency. The indicator of working hours attendance shows a decrease and has not yet reached optimal attendance. Meanwhile, the indicator of the level of employee attendance in participating in Morning Spiritual Gathering (MSG) activities and school activities also shows a decline. The contribution indicator in the successful activities of the New Student Admission (PPDB) is still very low. Overall, this data shows that employee performance at SMK MUTU needs to be further improved. This study aims to explore how reward, punishment, and leadership exemplary impact on organizational culture and employee performance. This study uses descriptive and verification methods to explore the relationship between reward, punishment, and leadership exemplary on organizational culture and employee performance. Data were collected through a questionnaire involving a sample of 108 employees selected through a saturated sample. Hypothesis testing using SEM-PLS analysis revealed a positive and significant effect of reward, punishment, and leadership example on organizational culture and employee performance. However, organizational culture has no effect on employee performance. Organizational culture does not mediate reward, punishment, and leadership exemplary to employee performance. These findings suggest that strengthening the reward system, implementing wise punishment, and strengthening the role of consistent leadership example are important strategies to improve employee performance.